2017
DOI: 10.1007/s10554-017-1152-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between cardiovascular disease risk scores and subclinical atherosclerosis prevalence in non-elderly adult patients from Argentina

Abstract: The goal of our study was to use statistical analysis to try to associate cardiovascular disease (CVD) risk scores and the observed prevalence of subclinical atherosclerosis (SA) in a non-elderly adult local population. An observational cross-sectional study was carried out (143 male and 131 female) on non-elderly adults (20-59 years). CVD risk scores included Framingham Risk Scores for 10-year hard (FRS 10 H), 30-year lipid hard or CVD (FRS 30 L H or FRS 30 L CVD), 30 year-body mass index hard or CVD (FRS 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
(34 reference statements)
2
7
1
1
Order By: Relevance
“…Consistent with previous research (35,37,41,42), males had a higher Framingham risk score than females. This might be due to the significantly higher SBP, and tobacco use among males.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous research (35,37,41,42), males had a higher Framingham risk score than females. This might be due to the significantly higher SBP, and tobacco use among males.…”
Section: Discussionsupporting
confidence: 91%
“…We found a high prevalence of increased CVD risk, i.e., Framingham risk score ≥ 10%, in this population. Our estimates were higher than those reported in Peru ( 34 ), Argentina ( 35 ) and Southern Brazil ( 20 , 36 ), similar to India ( 37 ), but lower than Honduras ( 38 ) and China ( 39 ). These differences might be explained by genetic, racial, sociodemographic, and cultural diversity, as well as the use of other versions of the Framingham risk score, with a varied set of predictors.…”
Section: Discussioncontrasting
confidence: 89%
“…Eight risk factors are incorporated in the Framingham algorithm: age, sex, HDL, total cholesterol, systolic blood pressure, diabetes mellitus (DM), antihypertensive treatment and current smoking status. Body mass index (BMI) can be used instead of lipid levels if these are not available and both models are found to predict CVD with high accuracy, though the calculation based on lipids seems superior (Albertini et al, 2017; Pencina et al, 2009b).…”
Section: Methodsmentioning
confidence: 99%
“…In this way, we found that decreased LRP1 expression at cell surface in total monocytes only correlated with total cholesterol and non-HDLc but not with LDLc in the totality of individuals studied, which may be related with the moderate increase of plasma LDLc observed in these subjects. In addition, although the age is a known risk factor for atherosclerosis development (1,2), in our study we observed that the age would be an independent factor for the LRP1 expression in total monocytes since it is decreased 10.3389/fcvm.2022.949778 in IR group but not in LR group with comparable ages in both groups. Taking into account our data, reduced levels of LRP1 at cell surface in circulating monocytes could be considered as a risk factor of atherosclerosis development in asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 47%
“…The detection by imaging methods of atherosclerotic plaques in arteries of asymptomatic individuals is termed subclinical atherosclerosis (SCA) ( 1 , 2 ). SCA represents the majority of cases among younger adults, who can suffer cardiovascular events despite being considered as low CVD risk score ( 1 , 3 ).…”
Section: Introductionmentioning
confidence: 99%